Transnasal administration of a combination of dexmedetomidine, midazolam and butorphanol produces deep sedation in New Zealand White rabbits. (4th June 2015) - Santangelo, Bruna; Micieli, Fabiana; Mozzillo, Tiziana; Reynaud, Fabiana; Marino, Francesco; Auletta, Luigi; Vesce, Giancarlo
Abstract: Objective: To study the sedative and cardiorespiratory effects of transnasal (TN) administration of a combination of dexmedetomidine (DEX), midazolam (MID) and butorphanol (BUT) administered through a nasal catheter to rabbits undergoing diagnostic procedures. Study design: Descriptive cross‐sectional experimental study. Animals: Eight healthy New Zealand White rabbit does (12 ± 1 months old, 3.5 ± 0.3 kg). Methods: DEX (0.1 mg kg −1 ), MID (2 mg kg −1 ) and BUT (0.4 mg kg −1 ) were mixed (DMB) in a syringe and applied to the rabbits' nasopharyngeal mucosa after the accurate catheterization of one nostril. The onset, duration and quality of effects including analgesia were scored using a numeric rating scale of sedation for rabbits. Continuous monitoring of vital parameters was performed via clinical and multiparametric recording. Physiological variables were explored using repeated measuresanova for parametric data or Friedman's test for non‐parametric data. Tukey's or Dunn's post hoc multiple comparisons test was used depending on normality. The statistical significance was set at p  < 0.05. Results: Loss of the righting reflex, deep sedation and profound analgesia ensued simultaneously at 1.4 ± 1.1 minutes after DMB administration. These effects lasted 45 minutes before subsiding into moderate sedation, which lasted for an additional 25 minutes. Residual central nervous system impairment persisted up to 100 minutes. Blood pressure dropped progressively over time by 50%, whereas respiratory frequency decreased by 70%, consistent with moderate hypoxemia and hypercarbia. Conclusion and clinical relevance: The TN route is a reliable and effective means for administration of DEX, MID and BUT to rabbits. The overall profound sedative effects and analgesic proprieties of the DMB combination can be selectively reversed depending on the needs of the procedure. Oxygen supplementation and careful monitoring are mandatory even in healthy subjects. The DMB protocol should be cautiously used in rabbits with cardiovascular or respiratory deficiencies.